Hubungan Gaya Belajar Terhadap Keterampilan Menulis Esai Kelas XI SMAN 9 Padang - Junaidi, Rissa Amelia Putri; Hartati, Yulia Sri; Pebriani, Yulia (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The aim of this study is to examine the correlation between the learning preferences and essay writing abilities among 11th-grade students at SMA Negeri 9 Padang in class XI F7 for the learning style questionnaire trial and class XI F5 for the learning style questionnaire test and essay writing skill test using a random sample with a total of 32 students. This research employs a quantitative approach utilizing the correlation method to investigate potential associations between the two variables, namely learning style variables and essay writing skills variables. The results of this study are that in the data requirements test, the data normality test and homogeneity test are carried out. The normality test for the two data obtained a value of 0.427> 0.05 for learning style and 0.068> 0.05 for essay writing skills so that the two variables are normally distributed. Furthermore, for the data homogeneity test, a value of 0.218> 0.05 was obtained so that the data was homogeneous. Then, the result of this research hypothesis is 0.002< 0.05, it can be inferred that a connection exists between the learning style and essay writing skills of class XI students of SMA Negeri 9 Padang.